Communication Networking : an Analytical Approach. - Kumar, Anurag (Morgan Kaufmann series in networking., 2004)
Covers fundamental concepts in detail and places design issues in context by drawing on real world examples from technologies in use. This book provides coverage of topics such as network calculus with deterministically-constrained traffic, congestion control for elastic traffic, packet switch queuing, switching architectures, and others.